Numerical Study of Alternate Bars in Alluvial Channels With Nonuniform Sediment. Issue 4 (12th April 2019) - Cordier, F.; Tassi, P.; Claude, N.; Crosato, A.; Rodrigues, S.; Pham Van Bang, D.
Abstract: Rivers typically present heterogeneous bed material, but the effects of sediment nonuniformity on river bar characteristics are still unclear. This work investigates the impact of sediment size heterogeneity on alternate bars with a morphodynamic numerical model. The model is first used to reproduce a laboratory experiment showing alternate bar formation with nonuniform bed material. Subsequently, the influence of sediment size heterogeneity on alternate bars is investigated distinguishing hybrid from free bars, definition based on the presence/absence of morphodynamic forcing, considering the results of nine scenarios. In four of them, a transverse obstacle is used to generate forcing. The computations are carried out with the Telemac‐Mascaret system solving the two‐dimensional shallow‐water equations with a finite element approach, accounting for horizontal and vertical sediment sorting processes. The results show that sediment heterogeneity affects free migrating and hybrid bars in a different way. The difference lies in the presence/absence of a migration front, so that distinct relations between bed topography, bed shear stress, and sediment sorting are obtained. Sediment sorting and associated planform redistribution of bed roughness only slightly modify free migrating bar morphodynamics, whereas hybrid bars are greatly impacted, with decreased amplitude and increased wavelength. Increased sediment size heterogeneity increases the degree of sediment sorting, while the sorting pattern remains the same for both free and hybrid bars. Moreover, it produces averagely higher, longer, and faster free bars, while in the case of hybrid bars their wavelength is increased but no general trend can be determined for their amplitude. Key Points: Free bars and hybrid bars show distinct topography, bed shear stress, sediment transport, and sediment sorting patterns Increased sediment heterogeneity induces longer free/hybrid bars, higher free bars but no general trend for the hybrid bar amplitude Sediment sorting does not impact the averaged free bar characteristics, while hybrid bars become longer and damped